HUBUNGAN ANTARA POLA ASUH ORANG TUA DAN PERGAULAN TEMAN SEBAYA DENGAN KARAKTER TANGGUNG JAWAB SISWA - M. Zaki Fauzil Hanif; Indhra Mustofa; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The inculcation of the character of responsibility is very important for students starting the process of maturation, parenting plays an important role in the formation of the character of responsibility in children, besides that other factors, namely the association of peers also affect the character of responsibility in students. This study aims to determine whether there is a relationship between parents and peer association with the character of student responsibility, whether there is a relationship between the quality of parents and students and whether there is a relationship between peer association and the quality of responsibility. This research uses correlational quantitative method. With a total sample of 83 from Class XI Science SMA Negeri 1 Bandar Sribhawono Lampung Timur. Data collection techniques in this study using a questionnaire or questionnaire method. the responsibility character scale is 22 items with reliability α=0.859, the parenting pattern scale is 18 items with reliability α = 0.772 and peer relationships are 18 items with reliability α=0.801. Based on the results of this study, it can be said: the value of R = 0.790 and the value of F = 66,235 with a significance level of P < .001, and for the second it provides an effective contribution (SE) of 62.3%. That is, There is a positive relationship between parenting patterns and the association of adolescent friends with the nature of student responsibility.The results of data analysis show the value of the correlation coefficient ( R〗_(x1-y)) = 0.737 with a significance level of P<.001, with a contribution effective by 42.156%. That is, the higher the parenting style, the higher the student's character. In addition, the value (R〗_(x2-y)) = 0.615 with a significance level of P<.001, with an effective contribution of 20.233%. This means that the higher the peer association, the higher the character of the student's responsibility.